Molecular Analysis and Prenatal Diagnosis of Segregating Β-Thalassemia - Jawaria Ishfaq, Amir Hamza Khan, Binish Sarwar Khan, Tariq Aziz, Faizan Khalid, Asia Noureen, Babar Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: This study aimed to comprehensively investigate the status of β-thalassemia mutational screening and prenatal diagnosis techniques in Pakistan, with a specific focus on understanding their implications for disease diagnosis and management. Methods: Blood and fetal samples were meticulously collected from three families affected by β-thalassemia. Employing the advanced Amplification Refractory Mutation System (ARMS) PCR technique, DNA isolation and amplification were carried out, leading to the identification of the three most prevalent β-thalassemia mutations—IVS-I-5, -619bp, and FSC 8-9—within these familial contexts. Results: The study unveiled the presence of the three predominant β-thalassemia mutations IVS-I-5, -619bp, and FSC 8-9 in the collected samples. These findings hold significant implications for the improvement of β-thalassemia diagnosis and management. Practical Implications: The identification of these common mutations has the potential to streamline genetic testing and prenatal diagnosis, potentially reducing β-thalassemia cases. Additionally, mutation analysis provides valuable insights into the disorder’s pathophysiology, enabling informed decisions and targeted genetic counseling for affected families to minimize transmission risk. Conclusion: In conclusion, this study constitutes a pivotal advancement in the ongoing efforts to mitigate the profound impact of β-thalassemia, both within Pakistan and on a broader global scale. By not only pinpointing the prevalent mutations responsible for the disorder but also delving into the techniques for diagnosis, the research lays a robust foundation for the enhancement of disease management strategies and preventive measures. Keywords: β-thalassemia; Chorionic villus sampling; ARMS PCR; Prenatal diagnosis; Mutation analysis; Disease prevention; Genetic counseling.